2015
DOI: 10.1002/2015gl066636
|View full text |Cite
|
Sign up to set email alerts
|

Mapping geoelectric fields during magnetic storms: Synthetic analysis of empirical United States impedances

Abstract: Empirical impedance tensors obtained from EarthScope magnetotelluric data at sites distributed across the midwestern United States are used to examine the feasibility of mapping magnetic storm induction of geoelectric fields. With these tensors, in order to isolate the effects of Earth conductivity structure, we perform a synthetic analysis—calculating geoelectric field variations induced by a geomagnetic field that is geographically uniform but varying sinusoidally with a chosen set of oscillation frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 49 publications
9
121
0
Order By: Relevance
“…In both regions considered here (Minnesota and Virginia), we estimated the maximum geoelectric field at two sites to be two orders of magnitude different despite being located in the same physiographic zones and proximal to one another. While Bedrosian and Love (2015) used a simple sinusoidal source, we have shown a similar result derived from observatory geomagnetic fields. Therefore, by considering the measured impedance at each site rather than applying a 1-dimensional conductivity model to a wide region, we can improve estimates of the behavior and amplitude of the geoelectric field and the corresponding risk to electric power grids.…”
Section: Implications For Geohazard Assessmentsupporting
confidence: 56%
See 2 more Smart Citations
“…In both regions considered here (Minnesota and Virginia), we estimated the maximum geoelectric field at two sites to be two orders of magnitude different despite being located in the same physiographic zones and proximal to one another. While Bedrosian and Love (2015) used a simple sinusoidal source, we have shown a similar result derived from observatory geomagnetic fields. Therefore, by considering the measured impedance at each site rather than applying a 1-dimensional conductivity model to a wide region, we can improve estimates of the behavior and amplitude of the geoelectric field and the corresponding risk to electric power grids.…”
Section: Implications For Geohazard Assessmentsupporting
confidence: 56%
“…These 1-dimensional conductivity models encompass large geographic regions of the USA which demonstrate considerable geologic complexity. Bedrosian and Love (2015) have demonstrated that such broad applications of these models to geologically complex regions do not remain consistent when evaluated against EarthScope impedances. These models do not consider the 3-dimensional effects of geoelectric induction when estimating the geoelectric field.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The former is generally the major factor affecting GIC magnitudes (Beggan, 2015). The latter leads to spatial variations of the electric field even if the magnetic field is a uniform plane wave (Bedrosian & Love, 2015). In case of nonuniform magnetic fields, lateral variations of the ground conductivity can locally play a further significant role (Beggan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The geoelectric field varies rapidly temporarily and spatially as demonstrated, for example, by Beggan et al (2013), Bedrosian and Love (2015), Wei et al (2013) and Wang et al (2016) for regional and continental scales, and by Püthe and Kuvshinov (2013) and Ngwira et al (2015) for global scales. Temporal variations are due to time variations of space currents and are connected with time variations of the geomagnetic field by Faraday's law.…”
Section: Introductionmentioning
confidence: 99%